Phytotea “ATINE” has beneficial effects on some neural, endocrine, immune, metabolic and biophysics variables in patients with maladaptation - Bombushkar, Igor; Gozhenko, Anatoliy; Savytskyi, Ivan; Popovych, Dariya; Badiuk, Nataliya; Anchev, Anatoliy; Duzhar, Viktor; Popovych, Igor (Journal of Education, Health and Sport, 2025)
Background and aim. Earlier we shown that phytotea “ATINE” enhances the immunomodulatory effect of adaptogenic factors of the Truskavets’ Spa in patients after radical treatment of oncological pathology. It is known that the main component of the balneotherapy complex of the Truskavets’ Spa – Naftussya bioactive water (NBAW) – has its own modulating effect on the parameters of the neuro-endocrine-immune complex, metabolism, acupuncture and biophotonics. The purpose of this study is to find out how the combined use of NBAW with ATINE will affect such effects as well as to estimate the essential effects of “ATINE”. Material and methods. The object of clinical-physiological observation were 10 men and 10 women aged 33-76 years with maladaptation (dysfunction of neuroendocrine-immune complex). The parameters of metabolism, EEG, HRV, acupuncture, biophotonics, cholekinetics, immunity, microbiota as well as adaptation hormones was assessed using routine methods, and two equal groups were formed on this basis. Members of the control group received NBAW for one week, while the main group additionally consumed the herbal tea “ATINE”. Results. The additional application of “ATINE” on the effects of NBAW in relation to a number of variables has an enhancing, weakening, reversing, and initiating effects, but is ineffective in relation to other variables. The essential effects of ATINE, calculated as algebraic differences between the effects of the two treatment regimens, can be summarized in the following blocks. Inhibitory: reduction in spectral power density of theta rhythm in C4, F4, C3, F3, T4 and O1 loci and beta rhythm in Fp1, C4 and T4 loci as well as LF band HRV; decrease in theta and alpha rhythm variability; decline in cortisol levels and systolic blood pressure, lowering in daily excretion of calcium, magnesium, and uric acid. Enhancing: increase in post-occlusive reactivity of systolic blood pressure, intensity of phagocytosis by neutrophils of Staph. aureus, fasting gallbladder volume, increase in serum levels of sodium, chloride and uric acid as well as activity of SOD and catalase. In addition, ATINE causes a leftward shift in the symmetry of alpha, beta, and delta rhythms as well as the electrical conductivity of the AVL acupuncture points, while a rightward shift in the symmetry of the fourth virtual Chakra. Conclusion. Phytotea “ATINE” has physiologically beneficial effects on the neuro-endocrine-immune complex and metabolism of patients with maladaptation.